Intense hurricane activity over the past 5,000 years controlled by El Nino and the West African monsoon - Donnelly, J. P.; Woodruff, J. D. (Nature, 2007)
The processes that control the formation, intensity and track of hurricanes are poorly understood. It has been proposed that an increase in sea surface temperatures caused by anthropogenic climate change has led to an increase in the frequency of intense tropical cyclones, but this proposal has been challenged on the basis that the instrumental record is too short and unreliable to reveal trends in intense tropical cyclone activity. Storm-induced deposits preserved in the sediments of coastal lagoons offer the opportunity to study the links between climatic conditions and hurricane activity on longer timescales, because they provide centennial- to millennial-scale records of past hurricane landfalls. Here we present a record of intense hurricane activity in the western North Atlantic Ocean over the past 5,000 years based on sediment cores from a Caribbean lagoon that contain coarse-grained deposits associated with intense hurricane landfalls. The record indicates that the frequency of intense hurricane landfalls has varied on centennial to millennial scales over this interval. Comparison of the sediment record with palaeo-climate records indicates that this variability was probably modulated by atmospheric dynamics associated with variations in the El Nino/Southern Oscillation and the strength of the West African monsoon, and suggests that sea surface temperatures as high as at present are not necessary to support intervals of frequent intense hurricanes. To accurately predict changes in intense hurricane activity, it is therefore important to understand how the El Nino/Southern Oscillation and the West African monsoon will respond to future climate change.
Donnelly, Jeffrey PWoodruff, Jonathan DengResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, Non-P.H.S.England2007/05/25 09:00Nature. 2007 May 24;447(7143):465-8.